2020
DOI: 10.1016/j.chemosphere.2019.125724
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of perfluoroalkyl substances in human milk from Ireland: Implications for adult and nursing infant exposure

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…The obtained LOQs for the target analytes varied from 5–50 ng kg −1 ( Table 1 ). Generally, these limits of quantitation are considered acceptable and mostly better than LOQs reported in the literature for similar matrices [ 10 , 11 , 20 , 21 , 26 , 35 ], considering that we practically demonstrated the LoQ values reported in this study, unlike the theoretical LOQ values mostly reported in literature. This displays the possibility of the application of the method to low-level regulatory detection of PFAS in milk and infant formulas [ 13 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The obtained LOQs for the target analytes varied from 5–50 ng kg −1 ( Table 1 ). Generally, these limits of quantitation are considered acceptable and mostly better than LOQs reported in the literature for similar matrices [ 10 , 11 , 20 , 21 , 26 , 35 ], considering that we practically demonstrated the LoQ values reported in this study, unlike the theoretical LOQ values mostly reported in literature. This displays the possibility of the application of the method to low-level regulatory detection of PFAS in milk and infant formulas [ 13 ].…”
Section: Discussionsupporting
confidence: 62%
“…Liquid chromatography with tandem mass spectrometry (LC–MS/MS) is the technique of choice for the analysis of PFAS, as it offers the advantages of high selectivity and provides (pseudo) molecular ion and sufficient product ions utilized for the unambiguous confirmation of individual PFAS, and offers the great sensitivity needed for low-level detection of PFAS [ 14 , 15 , 16 , 17 , 19 ]. Dairy milk is a complex matrix for the analysis of persistent organic pollutants such as PFAS, owing to its composition of proteins, sugars and lipids [ 20 , 21 ]. Since PFAS accumulate in both protein and fat [ 15 ], careful sample preparation techniques need to be employed for accurate identification and quantitation.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their extreme persistence, PFASs accumulate in the abiotic environment, e.g., ground [ 8 ] and surface water [ 9 ], soil [ 10 ], and air [ 11 ], as well as in the biotic environment [ 12 , 13 ]. Overall, there are large amounts of human exposure pathways so that PFASs can be detected in human serum [ 14 , 15 ] as well as in human breast milk [ 16 ]. The concerning notice that PFASs can be found ubiquitously, even in the arctic environment [ 17 ], and that there are potential negative effects on the environment and human health [ 18 ] lead to first limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Samples analysed in this study were collected between October 2016 and April 2018 as part of an Irish EPA funded research project (ELEVATE, reference 2016-HW-MS-8). The samples have previously been analysed for concentrations of brominated flame retardants [16] and Perfluoroalkyl substances [17] . The study population, approach to recruitment, sampling, and sample pooling are reported in detail in Wemken et al [16] , 2020.…”
Section: Human Milk Sample Collection and Poolingmentioning
confidence: 99%
“…The samples have previously been analysed for concentrations of brominated flame retardants [16] and Perfluoroalkyl substances [17] . The study population, approach to recruitment, sampling, and sample pooling are reported in detail in Wemken et al [16] , 2020. In brief, study recruitment and sampling protocols, adhered (with minor deviations) to WHO UNEP guidelines for developing a national protocol for measurement of POPs in human milk [13] and the study protocols of Pratt et al [15] , 2012.…”
Section: Human Milk Sample Collection and Poolingmentioning
confidence: 99%